Estimation of miRNA-21, miRNA-422, miRNA‐142-3p, and miR-181c Gene Expression as Potential Biomarkers of Osteoporosis in Premenopausal Women - Nahidah kzar madhloom; Maan Hasan Salih, Iktefa Abdul Hamid Mohammed saeed; Shimaa Jumaa Abood (Diyala Journal of Medicine, 2025)
Background: MicroRNAs (miRNAs) regulate several biological pathways in osteoporosis patients. The study aimed to estimate the correlation of miRNA-21, miRNA-422, miRNA‐142-3p, and miR-181c with osteoporosis in premenopausal women. Patients and Methods: This study was performed on 60 osteoporosis premenopausal and 30 healthy women. Determination of osteocalcin (OC), deoxypyridinoline (DPD), and bone-specific alkaline phosphatase (BAP) were done by ELISA, and estimation of miRNA gene expression was done by using qRT-PCR. Results: OC, DPD, and BAP levels indicated a significant decrease in osteoporosis women. In addition, our data showed that miRNA-21 (p=0.0001, r=-0.5585) and miRNA-422 (p=0.0035, r=-0.3715) have a high expression and negative correlation with BMD. Meanwhile, the miRNA-142-3p (p=0.0136, r=0.3089) and miRNA-181c (p=0.0401, r=-0.2685) have decreased expression and positive correlation with BMD value. Conclusion: The results of this study indicated a clear association of miRNA-21 and miRNA-422 in osteoporosis thus they may be useful as biomarkers for osteoporosis. Keywords: Osteoporosis, miRNA-21, miRNA-422, miRNA‐142-3p, and miR-181c.